How school leaders search for and use evidence. Issue 4 (2nd October 2018) - Fraser, Christie; Herman, Jayme; Elgie, Susan; Childs, Ruth A.
ABSTRACT: Background : Often, a principal's responsibilities include making decisions about the appropriateness of educational programmes to adopt in their school. Recommendations about programmes can be conflicting; so, a principal may need to search for evidence to inform their decision. Purpose : The purpose of this small-scale study was to clarify how school leaders search for, and use, evidence to inform programme adoption. We sought to answer three research questions: (1) how do principals search for evidence, (2) how do they use common sources and (3) what sources do they consider most useful? Sample : Twelve elementary school principals or vice-principals in Ontario, Canada participated in the study. Design and methods : In telephone interviews, the participants described how they would respond to a fictional decision-making scenario and rated different sources of evidence. Responses were analysed in depth, using a mixed-method approach, which involved coding principals' interview responses for themes and conducting a dual scaling analysis of their ratings of the usefulness of possible sources. Results : Principals report valuing formal sources of evidence such as reports and articles. However, in practise, findings indicated that they would turn to people first. Conclusions : School leaders prefer curated evidence from local educators to inform their decisions about the appropriateness of educational programmes for potential adoption.